Teacher Presence in Asynchronous Discussion Forums: Effects on the Level of Higher Education Students’ Interaction A study of Saudi context - Almousa, Samia (2016)
Currently, the number of higher education institutions utilising asynchronous online discussion forums (DFs) to support the interaction between students and their instructors is dramatically increasing. Teacher presence in the DFs has a crucial role in shaping student interaction; therefore, many scholars have attempted to investigate its impact on the level of students’ interaction. However, little research has scrutinised how the type and frequency of teachers’ contributions impact the level of student interaction using both qualitative and quantitative methods. For that reason, the researcher was eager to examine this impact by means of integrating the aforementioned methods in a Saudi context. A quasi- experimental methodology was applied to investigate the impact of the frequency and the types teacher’s contributions on the level of the students’ participation in the DFs. The researcher used the content analysis approach to see what types of the teacher’s posts impacted students’ interaction in the DFs. Data were collected through online observation (discussion forums’ transcripts) and from the students’ interviews. The researcher achieved some useful findings which hoped to prove helpful to readers, and especially educators, as this study is concerned with providing guidance to the teachers with regard to the extent to which instructor intervention is required to effectively encourage student participation and learning in the DFs. The findings show that the teacher’s presence in the DFs increased students’ interaction and decreased the amount of independent messages. Thus occurred because the teacher created an engagement, encouragement environment in the DFs. Further findings demonstrate that the different types of teacher’s posts in the DFs influenced the level of student interaction. Instructional design and organisation posts, facilitating discourse posts, encouraged students’ contributions. While the Direct instruction posts which included corrective feedback posts led to a decrease in the level of participation. In addition, the teacher’s presence in the DFs negatively impacted the level of student-to-student interaction since the students were focused on their teacher’s posts and directed their contributions toward her. In the presence of the teacher, the students did not attempt III to offer solutions for the issues their classmates faced, as they were worried they would undertake the teacher’s role when she was present. However, when the teacher invited all participants to provide their help to one of their classmates, peer-to-peer interaction significantly increased.